AN ACTIVE, SIGHT-THREATENING GRAVES’ ORBITOPATHY: A CHALLENGING CASE REPORT - Muhammad Fariz; Delfitri Lutfi; Ismi Zuhria; Susy Fatmariyanti; Hendrian Dwikoloso Soebagjo (Majalah Oftalmologi Indonesia, 2023)
Introduction: Graves’ Orbitopathy is a self-limiting autoimmune process associated with dysthyroid states, and if left untreated can lead to a number of complications, ranging from mild to sight-threatening. Corneal ulcer is one of the sight-threatening complications of Graves’ Orbitopathy. Case Report: A 22-year-old woman came with a complaint of blurred vision and retrobulbar pain on both eyes that happened gradually for 2 months, preceded by protrusion on both eyes. She had history of untreated hyperthyroid disease for 7 years. Her visual acuity was 1/60 and hand movement on the right and left eye, respectively. Anterior segment examination on both eyes revealed eyelids redness and swelling, redness and chemosis of conjunctiva, and corneal ulcer with descemetocele on her right eye. All of these clinical findings support the diagnosis of an active, sight-threatening Graves’ Orbitopathy. Discussion: The management of this patient involves; 1) thyroid function control due to the high level of thyroid function, 2) active, sight-threatening Graves’ orbitopathy management using high doses of intravenous methylprednisolon as guided by the 2016 European Group on Graves’ Orbitopathy (EUGOGO) guidelines protocol, 3) Application of amniotic membrane transplant to prevent the prolapse of intraocular tissue. Conclusion: By following EUGOGO guideline protocol, the clinical condition of this patient improved, but the management of an active, sight-threatening Graves’ Orbitopathy remains challenging and should be covered by multidisciplinary approach.